2008
DOI: 10.1080/02701367.2008.10599499
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Fitness in Obese Versus Nonobese 8–11-Year-Old Boys and Girls

Abstract: The purpose of this study was to compare cardiovascular fitness between obese and nonobese children. Based on body mass index, 118 were classified as obese (boys [OB] = 62, girls [OG] = 56), while 421 were nonobese (boys [NOB] = 196, girls [NOG] = 225). Cardiovascular fitness was determined by a 1-mile [1.6 km] run/walk (MRW) and estimated peak oxygen uptake (VO2peak) and analyzed using two-way analyses of variance (Gender x Obese/Nonobese). MRW times were significantly faster (p < .05) for the NOB (10 min 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Similar results were found in a study of 2927 children aged 5‐13 where the performance of overweight children on an endurance run test was significantly lower compared to healthy‐weight children 12 . Moreover, failing the cardiovascular test represented a major predictor of obesity among girls in the sample, a relationship that has been well established among children and adolescents in previous studies 49 . These findings bear on PE curriculum planning in that it is important to plan activities that enhance all components of physical fitness, and children's cardiovascular endurance in particular.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were found in a study of 2927 children aged 5‐13 where the performance of overweight children on an endurance run test was significantly lower compared to healthy‐weight children 12 . Moreover, failing the cardiovascular test represented a major predictor of obesity among girls in the sample, a relationship that has been well established among children and adolescents in previous studies 49 . These findings bear on PE curriculum planning in that it is important to plan activities that enhance all components of physical fitness, and children's cardiovascular endurance in particular.…”
Section: Discussionsupporting
confidence: 87%
“…The results were compatible with observations from other studies showing that overweight and obese youngsters tended to have poorer cardiovascular fitness than their normal-weight counterparts [32,33]. In view of the reporting bias of self-reported physical activity measures, we used cardiovascular fitness as a proxy and objective measure of physical activity in the study.…”
Section: Diet Overweight and Obesity In Adolescentssupporting
confidence: 92%
“…Mastrangelo et al [53] examined the running performance of OB children using a 1.6 km walk-run test and found that the running performance of OB children is lower. Significant differences were noted in terms of the body weight status when the minute oxygen consumption in ml per kg of body weight (48.3 in NW boys versus 41.6 in OB boys and 46.0 in NW girls versus 42.1 in OB girls) or the time to cover the distance (10 min, 34 sec in NW boys versus 13 min, 8 sec in OB boys and 13 min, 15 sec in NW girls versus 14 min, 44 sec in OB girls) composed the performance indicators.…”
Section: The Impact Of Excess Body Weight On Walkingmentioning
confidence: 99%